Currículo integrado no ensino médio: a percepção dos alunos do Instituto de Educação, Ciência e Tecnologia do Maranhão – IEMA - ROSA, Karyanne Moreira da Silva Nogueira (2019)
This research focus on integrated curriculum of a high school technical education from a professional school – the Institute of Education, Science and Technology of Maranhão (IEMA), the principal unit of IEMA located on Bacabeira city – and as the starting point the pursue of answers about the contribution of the curricular proposal of this Institute to the human formation and professional of its students. Besides that, it wants to analyze the curricular integration stipulated on the legal and pedagogical documents and how this integration materialize at school. The perception of the third year high school technical education students – individuals of this research – constitute a crucial issue to obtain the answers of the intended objectives obtained by the application of surveys and the focus group technique. This technique of research, split in four dimensions (perception of integrated curriculum; full time high school; sequence of studies; job market) allow to understand different perception of the students about integrated curriculum and its contribution to human formation and professional of those individuals. This is a qualitative research because it allow to seize the relation between social processes that not always show by immediate the perception of the individuals involved. The individuals participants of this research by filled the surveys were 96 students of third year high school technical education from IEMA, from Logistic, Administration and Mining technical course. The focus group was held with 10 students, also from third year high school technical education from IEMA and from the same course also mentioned. This research is based on studies of curriculum from the following authors: Bersntein (1996), Silva (2003), Frigotto (2004) e (2005), Santomé (1998), Lopes e Macedo (2011), Althusser (1980), Apple (2011), Ciavatta (2005), Lessard-Hébert, Goyette e Boutin (1990), Gadotti (2009), Giroux (1992), Kosik (1978), Lück (1994), Ramos (2005), Savianni (1990), besides others that gives us the theoretical support to made this research. Others documents that we based was on Modelo da Escola da Escolha of Instituto de Corresponsabilidade pela Educação (ICE), that are guiding of the Pedagogical Proposal of IEMA. After the analysis of the students dialogues with the theoretical reference study by us, we conclude that: the perception of the integrated curriculum on full time high school of IEMA, shows a curriculum that provide the professionalization related to a human integrated formation materialize on Life Project; the enthusiasm of the students on study in a full time school with a good infrastructure; the students visualize the university education as a possibility of social growth, cultural and personal, as well a possibility to enter in the job market to help the family to improve their financial and social conditions. However, we understand that the proposal of integrated curriculum on full time school at IEMA, develop on a capitalist society which the curriculum can perform its emancipatory function, but as well, it control function articulate to the school practices express on the speech and materialize on communicative interactions.